Quality analysis of YouTube videos on vulvodynia. Issue 1 (12th January 2023) - Aglamis, Savas Ozgur; Senel, Samet; Koudonas, Antonios
Abstract: Background: Social media, with its low cost and easy accessibility, represents an ideal medium for sharing medical interests, but the quality of its content is questionable. Aim: The primary aim of this study was to evaluate the quality of video content related to vaginismus on YouTube as a source of information by using scores of established classification systems. The secondary aim was to examine the relationship between objective and subjective measures of their quality. Methods: The term vaginismus was typed into the YouTube search bar (http://www.youtube.com ). The first 50 videos with the highest number of views were included in the study. All videos were assessed on August 18, 2022, by a gynecologist and/or a urologist experienced in vulvodynia. Data of all the videos were recorded, such as source, content, duration, day since upload date, number of views, number of likes, number of comments, and views per day. The Global Quality Scale (GQS) and modified DISCERN score were employed to assess the quality of the videos. Outcomes: The primary outcomes of this study were the scores of established classification systems and the measures relating to the preference and evaluation of viewers of YouTube videos on vulvodynia. Results: A total of 50 videos were evaluated. The sources of 32 (64%) of these videos were "universities/professional organizations/nonprofit physicians/physicians" and "stand-alone health information websites." The GQS and modified DISCERN scores of the videos whose source was "universities/professional organizations/nonprofit physicians/physicians" were higher than those whose source was "talk show programs/television programs" ( P  = .014 for GQS score, P  = .046 for modified DISCERN score). When classified according to GQS score, the quality level of 58% of the videos was low. Of the videos whose source was "universities/professional organizations/nonprofit physicians/physicians, " 56.3% were of good quality. Clinical Implications: The quality of information was very low and suggested that health care professionals should take on a more active role in configuring the qualitative characteristics of the material available online about the given health issues. Strengths and Limitations: To the best of our knowledge, this is the first study to investigate the quality of YouTube videos on vaginismus (vulvodynia). However, the limitation of this study is the relatively subjective evaluation of videos, including the risk of observer bias, although we attempted to overcome this problem with the inclusion of 2 independent reviewers and the use of validated tools. Conclusion: YouTube videos may offer a huge amount of information about this condition, but the quality of the available sources is heterogeneous.